Environmental impact assessment performance in an african context: case studies from Southern Africa (South Africa, Namibia, Malawi, and Tanzania) - Aljareo, Abdulhakim (University of the Witwatersrand, Johannesburg, 2024)
The Environmental Impact Assessment (EIA) system is a worldwide environmental policy tool, which has been introduced and adopted both in developed and developing countries. The EIA system is internationally acknowledged as an essential instrument to support sound decision-making in pursuit of sustainable development. Many countries have established the requirement for EIAs in their respective environmental legislative frameworks. However, considerable concerns are often raised about the inadequate performance of the EIA system in developing countries. The African developing countries have introduced EIA as an environmental policy implementation tool to their environmental policy and legal framework for environmental protection and management, as well as sustainable development promotion. However, the EIA system performance in the African developing country context is regarded as limited. The country context of the developing countries has been perceived to influence the performance of the EIA system. Fundamentally, the assessment of EIA system performance focuses on particular key EIA systemic components and EIA report, having limited consideration of the country context influence on the EIA system performance, and so does not provide a thorough understanding of the real causes of the limited EIA performance in the African context. Focusing on the EIA system performance in the African developing country context, an evaluation approach for EIA system performance and country context was developed. The developed approach was applied to four case studies from the southern African context (South Africa, Namibia, Malawi, and Tanzania). This was to evaluate EIA system components, EIA report, and country context. The research findings indicate that EIA system performance is limited due to the influence of the context of the case study countries. It was found that, despite the presence of the EIA legislative frameworks, EIA competent authorities, EIA procedural steps, and EIA reports in the case studies, different shortcomings have been identified such as misinterpretation of EIA provisions, limited EIA timeframes, incomprehensive EIA guidelines, insufficient provisions for conducting EIA follow-up and auditing. A further finding was the insufficient EIA report legal requirement which mirrored in the inadequate quality of the evaluated EIA reports. The most important v finding of this research is that EIA system performance depends on its country context. There is a clear relationship between country context of the case studies and EIA system development, implementation, and enforcement, thereby influencing EIA system performance. The key country context elements that were found to affect EIA system performance are the country legal, political, and socio-economic context, and the EIA stakeholders’ capacity. The consequences of the limited EIA stakeholders ‘capacity coupled with the inadequate country legal context due to insufficient laws to support justice in the administrative decisions, and access to information, had a significant impact on EIA system implementation and enforcement. The developmental state pressure on the EIA administration due to socio-economic challenges associated with political context issues such as interference and pressure also affected EIA system implementation and enforcement. The EIA system development was also influenced by the development state presented by the demand for economic development due to issues such as poverty and unemployment and the lack of political will and commitment to the EIA system. Based on this, a comprehensive understanding of the relationship between EIA system performance and the country context in Africa is required which can be achieved by using the developed evaluation approach in this study, to identify the possible measures for improving EIA system performance.
A thesis submitted in fulfilment of the requirements for the degree of Doctor of Philosophy to the Faculty of Science, School of Animal, Plant and Environmental Sciences, University of the Witwatersrand, Johannesburg, 2023
Keywords: Environmental Impact Assessment (EIA); Evaluation approach; Performance; Sustainable cities and communities; Life on land